2012
DOI: 10.1074/jbc.m112.410936
|View full text |Cite
|
Sign up to set email alerts
|

Rab26 Modulates the Cell Surface Transport of α2-Adrenergic Receptors from the Golgi

Abstract: The molecular mechanisms underlying the transport from the Golgi to the cell surface of G protein‐coupled receptors (GPCRs) remain poorly elucidated. Here we determined the role of Rab26, a Ras‐like small GTPase involved in vesicle‐mediated secretion, in the cell‐surface export of α2‐adrenergic receptors (α2‐ARs). We found that transient expression of Rab26 mutants and siRNA‐mediated depletion of Rab26 significantly attenuated the cell‐surface numbers of α2A‐AR and α2B‐AR as well as ERK1/2 activation by α2B‐AR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
83
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 48 publications
(88 citation statements)
references
References 53 publications
(67 reference statements)
3
83
1
1
Order By: Relevance
“…All three ␣ 2 -ARs couple to the Gi/Go family G proteins, and their activation has been well shown to stimulate the mitogen-activated protein kinases (MAPK) ERK1/2, inhibit adenylyl cyclases, and suppress voltage-gated calcium channels (24,26,(37)(38)(39). To investigate if GGA3 knockdown-induced reduction of cell surface ␣ 2B -AR expression could result in a concomitant defective signaling, the activation of ERK1/2 and the reduction of cAMP production were chosen as functional readouts.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All three ␣ 2 -ARs couple to the Gi/Go family G proteins, and their activation has been well shown to stimulate the mitogen-activated protein kinases (MAPK) ERK1/2, inhibit adenylyl cyclases, and suppress voltage-gated calcium channels (24,26,(37)(38)(39). To investigate if GGA3 knockdown-induced reduction of cell surface ␣ 2B -AR expression could result in a concomitant defective signaling, the activation of ERK1/2 and the reduction of cAMP production were chosen as functional readouts.…”
Section: Resultsmentioning
confidence: 99%
“…HEK293 cells were grown on coverslips precoated with poly-L-lysine in 6-well plates and transfected with 50 ng of ␣ 2B -AR-GFP together with 400 ng of control or GGA3 shRNA. The cells were permeabilized with PBS containing 0.2% Triton X-100 for 5 min and blocked with 5% normal donkey serum for 1 h. The cells were then incubated with antibodies against p230 (1:100 dilution) for 1 h. After washing with PBS (3 times for 5 min), the cells were incubated with Alexa Fluor 594-labeled secondary antibody (1:2,000 dilution) for 1 h. Images were captured using an LSM510 Meta Zeiss confocal microscope as described previously (24,33). To detect the cell surface expression of inducibly expressed HA-␣ 2B -AR, the cells were stained with anti-HA antibodies (1:500 dilution) without permeabilization.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have found that RAB26 is associated with RAB11 recycling endosomes (Chan et al, 2011) in Drosophila neurons, and a giantin-positive Golgi sorting compartment (Li et al, 2012) when transfected into HEK293 cells. These results would seem to contradict those presented here, although we have focused here exclusively on exocrine secretory cells, trying to mimic the effects of scaling RAB26 as occurs in differentiating cells in tissue.…”
Section: Discussionmentioning
confidence: 99%
“…S1B-F). The lack of RAB26 association with the Golgi was of interest, because recent studies have demonstrated that RAB26 might occupy a recycling endosomal (Chan et al, 2011) or giantin-positive Golgi compartment (Li et al, 2012). Because of the proximity, if not substantial direct overlap, of RAB26 vesicles with our trans-Golgi marker, we next examined membrane compartments that interact with the trans-Golgi.…”
Section: Rab26 Localizes Specifically To Lamp1 Lysosomal Membraneassomentioning
confidence: 99%